Effect of Complex Korean Medical Treatment on Spinal Epidural Hematoma: A Case Report - Youn Young Choi; Young Kyung Kim; Eun Sol Won; Chae Hyun Park; Hwa Yeon Ryu; Jae Hui Kang; Hyun Lee (MEDrang Inc., 2023)
This paper presents the clinical outcome of an 82-year-old female who experienced sudden back pain combined with lower limb paresthesia and weakness after epidural steroid injection. The magnetic resonance imaging of the thoracolumbar spine showed a spinal epidural hematoma (SEH) extending from T8 to L4. She was treated non-operatively in the traditional Korean medicine (TKM) hospital. The patient's progress was assessed using the Numerical Rating Scale (NRS), American Spinal Injury Association (ASIS), Spinal Cord Independence Measure version III (SCIM III), and self-reported symptoms. During the 22-day hospitalization period, the NRS score decreased from 7 to 2 points, the motor score on the ASIS scale increased from 65 to 95 points. The subjective sense of lower extremities was felt by 1 increased to 8. The SCIM III score increased from 32 to 69 points. These results suggest that TKM could effectively reduce pain and aid the rehabilitation of patients with SEH.